APPLICATION OF THE WORKLOAD INDICATORS OF STAFFING NEED METHOD IN ACHIEVING HOSPITAL SERVICE QUALITY IN DEVELOPING COUNTRIES: SYSTEMATIC LITERATURE REVIEW - Yusnita Wardani; Sopiah; Noviarakhman Zagladi, Arief (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2024)
Phenomenon/Issue: This research is not only related to WISN to measure the level of workload but how the results of this WISN methodology can be used as an evaluation of the achievement of hospital service quality, especially in this study are hospitals in developing countries. Purpose: This study aims to find out how the application of the WISN method in developing country hospitals in achieving hospital service quality. Novelty:This research only focuses on the results of existing research in developing countries so it cannot be generalized. Research Methods:This study uses the SLR method to collect articles related to the implementation of WISN in developing countries published between 2019 and 2024. Results: The application of the WISN method in hospitals in developing countries is very effective in determining the shortage of labor that results in an increased workload, so that performance is not optimal. Management is needed that can organize or allocate labor according to workload analysis. In addition, to optimize the workforce, it is necessary to carry out training to improve the competence of the workforce, because the quality of the workforce affects the achievement of the quality of hospital services. Research Contributions: With this study, it can be used by hospitals as a consideration in evaluating their health workforce in terms of number and competence.